Exequies for the death of a Royal Angel. The funerary mound of queen María de las Mercedes in the temple of the Professed in Mexico City: An allegation to the Spanish Monarchy - Fernández Paradas, Antonio Rafael; Sánchez Guzmán, Rubén (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
After the unexpected death of the queen María De Las Mercedes of Orleans on June 26, 1878, signs of pain and respect were experienced both inside and outside the kingdom. Of special importance were the funeral rites and the symbolic apparatus that the Spanish colony of Mexico city offered for the queen’s rest in the temple of the professed in the Mexican main city. The objective of this work is to analyze the artistic and iconographic values of the ephemeral decorations made in mexico city, on the occasion of the death of the wife of the king Alfonso XII.